Dollar funding and housing markets: The role of non-US global banks - Torsten Ehlers; Mathias Hoffmann; Alexander Raabe (University of Zurich, Department of Economics, 2025)
Non-US global banks are an important driver of the international synchronization of house price growth. A loosening (tightening) of US dollar funding conditions leads non-US global banks to expand (contract) their international lending, which is largely denominated in US dollars. This induces a synchronization of lending across borrowing countries, which translates into an international synchronization of house price growth. Borrowing country pairs whose joint exposure to US dollar funding conditions via their non-US creditor banks (dollar co-dependence) is higher, exhibit a higher synchronization of house price growth. Our results identify a novel international spillover channel of US dollar funding conditions, which is not related to common-lender exposures. We show theoretically and empirically that the exposure of non-US global banks to dollar funding conditions is captured by the bilateral treasury basis between the currency of the non-US global creditor banks' headquarters and the US dollar. As these conditions vary over time, borrowing country pairs whose non-US global creditor banks are more exposed to US dollar funding variations exhibit higher house price synchronization.
Keywords: F34; F36; G15; G21; 330; house prices; synchronization; US dollar funding; global US dollar cycle; US treasury basis; convenience yield; global imbalances; capital flows; global banks; global banking network